2008
DOI: 10.1016/j.jasms.2008.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Electron capture and transfer dissociation: Peptide structure analysis at different ion internal energy levels

Abstract: We decoupled electron-transfer dissociation (ETD) and collision-induced dissociation of charge-reduced species (CRCID) events to probe the lifetimes of intermediate radical species in ETD-based ion trap tandem mass spectrometry of peptides. Short-lived intermediates formed upon electron transfer require less energy for product ion formation and appear in regular ETD mass spectra, whereas long-lived intermediates require additional vibrational energy and yield product ions as a function of CRCID amplitude. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 41 publications
3
58
0
Order By: Relevance
“…The H t values of each peptide are shown in column 2 of [2,16,18]. Furthermore, it has been reported that collisional activation of the charge reduced species [M ϩ 2H] ϩ· can improve fragmentation efficiency and increase relative amounts of the c ϩ· and z= ϩ ions in ETD [19].…”
Section: Resultsmentioning
confidence: 99%
“…The H t values of each peptide are shown in column 2 of [2,16,18]. Furthermore, it has been reported that collisional activation of the charge reduced species [M ϩ 2H] ϩ· can improve fragmentation efficiency and increase relative amounts of the c ϩ· and z= ϩ ions in ETD [19].…”
Section: Resultsmentioning
confidence: 99%
“…ECD FT-ICR MS of six doubly protonated horse myoglobin tryptic fragments ( [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], [32][33][34][35][36][37][38][39][40][41][42] Figure S2) and with vibrational activation ( Figure 5) confirm preferential and sometimes periodic product ion formation from peptides with mainly ␣-helical or ␤-turn secondary structure in solution (before protein digestion). Predominantly z-ions are observed because of preferential charge retention at the C-terminal Lys or Arg basic residue upon electron capture, as expected for doubly charged tryptic peptides.…”
Section: Ecd Of Doubly Charged Amphipathic Peptidesmentioning
confidence: 99%
“…Therefore, we selected the class of amphipathic peptides and proteins to probe ECD characteristics, to improve both fundamental and practical aspects of ECD in MS/MS. Projection of ECD Fourier transform ion cyclotron resonance (FT-ICR) MS results to ETD in ion trap MS is considered as a second step and will require estimation of ion cooling at the higher pressure of ETD experiments [36].…”
mentioning
confidence: 99%
“…Among these excluded sites, the site on Ser230 of G3BP1 and the site on Thr399 of SRC8 proteins were assigned to be phosphorylation sites in previous reports [29,30] without confirmation. It is worth noting that the synthetic peptides shown in Figures 2b and 3b without and with dimethyl labeling, respectively, were the same sequence (SSpSPAPADIAQTVQEDLR) derived from Ras-GTPase-activating protein-binding protein 1 as shown in Figure 4a, whereas, unlike those detected from the synthetic peptides, no y 16 or y 17 ions (Figure 4a) could be detected from A431 cells to help in identifying the exact phosphorylation site. Likewise, the synthetic peptide shown in Figure 3c is the same sequence (TQpTPPVSPAPQPTEER) derived from Src substrate cortactin as that displayed in Figure 4b but with different phosphorylation sites.…”
Section: Mapping and Quantifying Phosphorylation Sites In Vivomentioning
confidence: 99%